Makna Kenabian dalam Tafsir Ath-Thabari - Zulaiha, Siti (Syams, 2023)
Prophethood is a grace given to Allah SWT chosen man called a prophet. MostMuslims know that there are 25 prophets who must be trusted and believed in theirprophethood. Ibn Jarir Ath-Thabari's interpretation of Tafsir Ath-Thabari makesno explicit mention of the prophethood of Dzulkifli. Prophetic in Arabic isnubuwwah which has the origin of the word naba'a (news). Prophetic is someone whoconveys news and information from Allah Almighty. The news that was conveyedwas mostly related to the same thing. So in the story of Khidir in QS al-Kahfi, somescholars call him a prophet. Whereas in the tafsir ath-Thabari, Khidira believed andtaught him about the unseen (ghaib). Therefore, the author tries to emphasize thereality of diversity in interpreting prophethood. This research is a literature researchthat uses Hans-Georg Gadamer's hermeneutic analysis. Using this analysis, theauthor found that tafsir Ath-Thabari was written in the phenomenon of people notunderstanding the Qur'an well. The result of the fusion between the two horizons is:prophetic according to ath-Thabari is something that Allah gave to His chosen mansent for man with bright evidence from the Qur'an and hadith. In the modern-era, noone can be a prophet. The prophetic period has closed with the prophethood ofMuhammad SAW. Even more so with the convenience that can be obtained in thepresent time of sophistication of digital.